2022
DOI: 10.1371/journal.pbio.3001841
|View full text |Cite
|
Sign up to set email alerts
|

Finding logic models for sustainable marine development that deliver on social equity

Abstract: Sustainable development is often represented as contributing to desirable outcomes across economic, environmental, and social goals, yet policies and interventions attempting to deliver sustainable development often disagree on the order in which these categories of goals should be addressed. In this Essay, we identify and review 5 approaches (called logic models) for sustainable development in ocean systems based on existing policies and interventions and consider the evidence for their contributions to equit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…Policy goals are general ideas at the macro‐level governing policy development, which are a basic and fundamental component of any public policy (Howlett & Cashore, 2009, 2014; Petek et al, 2021). Compared to other policy goals such as economic efficiency and environmental sustainability, social equity goals are often not clearly specified in public policies and are lacking appropriate evaluative measures (e.g., see the discussion of integrating social equity in transportation policy goals by Manaugh et al (2015) and in sustainable marine development policy goals by Ota et al (2022)). For renewable energy policies, the three “E” goals (secure energy supply, reduce environmental pollution, and economic affordability) are often examined in the literature (Komor & Bazilian, 2005; Schmidt et al, 2019; Shen et al, 2011), while not much attention has been on social equity goals.…”
Section: Integrating Equity In Public Policy Designmentioning
confidence: 99%
“…Policy goals are general ideas at the macro‐level governing policy development, which are a basic and fundamental component of any public policy (Howlett & Cashore, 2009, 2014; Petek et al, 2021). Compared to other policy goals such as economic efficiency and environmental sustainability, social equity goals are often not clearly specified in public policies and are lacking appropriate evaluative measures (e.g., see the discussion of integrating social equity in transportation policy goals by Manaugh et al (2015) and in sustainable marine development policy goals by Ota et al (2022)). For renewable energy policies, the three “E” goals (secure energy supply, reduce environmental pollution, and economic affordability) are often examined in the literature (Komor & Bazilian, 2005; Schmidt et al, 2019; Shen et al, 2011), while not much attention has been on social equity goals.…”
Section: Integrating Equity In Public Policy Designmentioning
confidence: 99%
“…The notion of sustainable economic development signifies a substantial paradigm shift in our approach to growth and progress. It is a response to the crucial challenges posed by traditional development models that frequently prioritize economic growth at the cost of environmental health and social equity [1]. It integrates economic, environmental, and social considerations, aiming for a balance of long-term sustainability and fairness [2].…”
Section: Introductionmentioning
confidence: 99%
“…Some, for instance, emphasize conservation, ocean protection, or innovation and new technology (Voyer et al, 2018). Others focus on the economic, social, and political promotion of marginalized groups, thus bringing them in line with the emphasis on "no one left behind" (Ota et al, 2022) found in the United Nations Sustainable Development Goals (for example see, Voyer et al, 2018;Fusco et al, 2022).…”
Section: Introductionmentioning
confidence: 99%